Helminth infections in apodemus sylvaticus in southern England: interactive effects of host age, sex and year on the prevalence and abundance of infections - Behnke, J.M.; Gilbert, F.S.; Zain, S.N.M.; Lewis, J.W. (1999)
Helminth parasites were studied in the wood mouse, Apodemus sylvaticus, in southern England in September of each of four successive years (1994-1997). Nine species of helminths were recorded: five nematodes (Heligmosomoides polygyrus, Syphacia stroma, Pelodera strongyloides, Trichuris muris, Capillaria murissylvatici), two cestodes (Microsomacanthus crenata, Taenia taeniaeformis) and two trematodes (Corrigia vitta, Brachylaemus recurvum). In total, 134 mice were examined and 91.8% carried at least one species of helminth. The majority of mice carried two to three species (60.5%) and the highest combination was six of the nine species recorded in the study. The patterns of between-year variations in the prevalence and abundance of infection were different for each of the six species for which sufficient quantitative data were available to enable statistical analysis. For H, polygyrus, the most important source of variation arose from between-year differences, host age and. the interaction of these factors: abundance increased with host age but in 1995 the age pattern was markedly different from that in the remaining years. The abundance of C. vitta also varied significantly between years but additionally there was a strong independent age effect. For M. crenata, the year x age interaction was significant, indicating that abundance among different age cohorts varied from year to year but there was also a weak significant main effect of age arising from the youngest age cohort carrying no parasites and the oldest age cohort the heaviest infections. For P, strongyloides the only significant factor was between-year variation with 1995 being a year of exceptionally low prevalence and abundance of infection. No significant between-year variation was detected for S. stroma but there was a strong sex effect (males carrying heavier infections) and an age effect (older mice of both sexes carrying heavier infections). The abundance of Trichuris muris varied only in relation to host age, worm burdens growing in intensity with increasing age, but there was also a significant interaction between year and host sex with respect to prevalence. For the remaining three species, the prevalence of infections was too low (<8.2%) to enable any meaningful interpretation. This analysis emphasizes the need for carefully controlled statistical procedures in aiding the interpretation and the prioritization of the factors affecting worm burdens in wild rodents.